Implementering av forskningsbasert bacheloreksamen i sykepleie – prosess og erfaring - Michaelsen, Ragnhild; Skrondal, Torill; Thylén, Ingela (Nordisk tidsskrift for helseforskning, 2015)
Implementation of a research-based bachelor thesis in nursing – process and experiencesBackground: Ability to ensure quality and to evaluate own practice of nursing, is essential in order to practice a research based health care. An increase of research skills among future nurses, are thus central. The aim of this paper is to describe experiences connected with implementation of a new research-based model for examination of bachelor thesis in bachelor degree in nursing at Molde University College, Norway.Results: The curriculum has gained a clearer focus on science and research, and informative guidelines have been developed. The final bachelor thesis is now consisting of a systematic literature review based on scientific articles. The auditorium as a learning arena in the form of a thesis defence contributes to awareness of importance of research for nursing.Conclusion: The introduction of a new research based model for the bachelor thesis has strengthened the academic environment. Currently, Bachelor of Nursing has a clear focus on research and development. Newly qualified nurses are well placed to work knowledge based and to participate in development of clinical practice.
Keywords: bacheloreksamen; implementering; evidensbasert sykepleie; utdanning; bachelor thesis; implementation; evidence-based nursing; education